The effect of strong carbide-forming elements on the adhesive wear resistance of ferritic stainless steel - Aksoy, M; Yilmaz, O; Korkut, MH (Elsevier Science Sa, 2001)
The influences of strong carbide-forming elements such as Mo, Ti, V, Nb and homogenization on the adhesive wear resistance of ferritic stainless steels (18 wt.% Cr) have been studied. The wear behavior of the homogenized and unhomogenized samples was investigated in a block-on-ring apparatus under the loads of 40, 60 and 80N, respectively. The results of dry sliding tests were interpreted as taking the properties of the samples such as microstructure, surface hardness, and grain boundary energies into account. It has been found that, homogenization heat treatment decreased the weight losses. It was also observed that, except S3 for all of samples the total weight losses was changed in compatible aspects with microhardness, toughness and grain boundary energies. However, this relation could not be established between surface hardness and total weight losses. Among all of the samples, the best result has been found from the samples containing V and Mo. In addition, the samples, which consist Of M23C6 carbides in their microstructures without carbide-forming elements, gave good wear resistance under the load of 40 N. (C) 2001 Published by Elsevier Science BN.
Keywords: ferritic stainless steels; adhesive wear; strong carbide-forming elements